Promene β2 mikroglobulina i elektrolita u različitim fazama COPD-a i njihove vrednosti u proceni prognoza: β2-microglobulin, electrolytes in COPD: Prognostic significance - Wang, Lin; Yi, Rong; Wei, Lanlan; Xiong, Jiali (Journal of Medical Biochemistry, 2024)
Background: To investigate the changes of β2-microglobulin and electrolyte in different stages of chronic obstructive pulmonary disease (COPD) and the value of evaluating prognosis. Methods: A retrospective study was undertaken on 120 patients diagnosed with COPD and treated at our hospital between February 1, 2020, and January 31, 2023. These patients were classified into three groups based on the GOLD classification: mild (FEV1 > 81%), moderate (51% < FEV1 ≤ 80%), and severe (FEV1 ≤ 50%). As a control group, 40 healthy individuals who had routine examinations during the same period were selected. The COPD patients were then followed up and divided into a good prognosis group (n = 67) and a poor prognosis group (n = 53). The levels of β 2-microglobulin and electrolytes were measured in patients with different stages of the disease and different prognoses. Kendall’s tau-b and ordered logistic regression were employed to analyze how the changes in β 2-microglobulin and electrolyte levels correlated with disease severity. Furthermore, the prognostic value of β 2-microglobulin and electrolyte levels in COPD was assessed using an ROC curve. Results: In comparison to the control group, the severity of COPD patients displayed a notable increase in β 2-microglobulin levels, while there was a significant decrease in levels of calcium, chlorine, potassium, and sodium. Kendall’s tau-b correlation coefficient analysis indicated a positive correlation between COPD severity and β 2-microglobulin, and a negative correlation between COPD severity and levels of calcium, chlorine, potassium, and sodium. Logistic regression analysis revealed that there was a positive correlation between disease severity and β 2-microglobulin, and a negative correlation between disease severity and levels of calcium, chlorine, potassium, and sodium. Furthermore, the poor prognosis group exhibited a significant increase in β 2-microglobulin levels, alongside a significant decrease in levels of calcium, chlorine, potassium, and sodium compared to the good prognosis group (P < 0.05). ROC curve analysis demonstrated that a combined detection of β 2-microglobulin, calcium, chlorine, potassium, and sodium yielded significantly higher area under the curve, sensitivity, and specificity values compared to single detection methods, highlighting its significant predictive value for COPD prognosis. Conclusion: Patients who presented with a more severe form of the disease exhibited elevated levels of β 2-microglobulin and reduced electrolyte levels. Prognostic accuracy was significantly enhanced when β 2-microglobulin and electrolyte levels were analyzed together, offering a superior method for predicting patient outcomes.